FEATURES OF THE QUALITY OF LIFE OF PATIENTS WITH CHRONIC RENAL FAILURE IN THE TREATMENT OF HEMODIALYSIS - Khusainova Munira Alisherovna; Kamolova Diyora Jamshedovna; Yarmatov Suvon Totlibayevich; Gafforov Xudoyor Xudoyberdiyevich (Journals Park Publishing, 2022)
Chronic renal failure is a consequence of many kidney diseases and is quite common in medical practice. The use of modern methods of detoxification renal replacement therapy (hemodialysis, peritoneal dialysis) has allowed to increase the life expectancy of patients with end-stage chronic renal failure by an average of 10-12 years, even without kidney transplantation. However, despite the improvement of therapy, the prospect of lifelong dialysis treatment is still accompanied by numerous fears and concerns on the part of patients who are going to receive this treatment. Among patients diagnosed with uremia, the idea of dialysis as the end of life is often found. And even when, from a medical point of view, treatment is successful and life acquires a real perspective, returning to a normal, full-fledged life can become a serious psychological problem for the patient. Treatment with chronic hemodialysis (HD) is associated with a constant somatogenic vital threat, leads to serious changes in the physical, psychological and social spheres. Renal pathology at the stage of terminal renal failure, being a typical chronic disease, is at the same time unique due to the specifics of treatment. We can say that a new, "artificial" form of life is being formed, supported by the purification of the patient's blood from toxic metabolic products during HD sessions. There are patients who have the life expectancy on dialysis exceeds the life expectancy before dialysis. However, attachment to the "artificial kidney" device, the need to spend a lot of time on hemodialysis sessions, restriction of freedom of movement, strict diet, the need to sharply reduce fluid intake, disability, lack of communication, change in appearance – all these are powerful traumatic factors accompanying the treatment of HD.
Keywords: Chronic renal failure, hemodialysis, quality of life